MERKEL CELL CARCINOMA – REPORT OF 7 CASES - Cabral, Rita (2014)
Introduction: Merkel cell carcinoma is a rare, aggressive cutaneous neuroendocrine carcinoma that affects primarily elderly people. Patients present with a rapidly growing nodule, preferably located at the head, neck and limbs. Merkel cell carcinoma as a propensity for local recurrence and regional lymph node metastases and wide local excision is the initial consensual approach. The role of lymph node dissection, radiation therapy and chemotherapy is not yet clearly established. Material and Methods: The aim of this retrospective study was to evaluate Merkel cell carcinoma patients followed in our department between the years 2000 and 2009, regarding sex, age, race, clinical features, location, stage, associated malignancies, treatment and evolution.  Results: Our data are consistent with the literature, namely regarding age, associated lymphoproliferative disease and high local recurrence and mortality rates.